A Study on the Function of Laparoscopy to Identify the Etiology of Infertility - Hema , K. R.; Lalitha , H. S. (Novel Research Aspects in Medicine and Medical Science Vol. 1, 2023)
This study was conducted to assess the role of diagnostic laparoscopy in the investigation of female infertility and to evaluate the various causes of infertility like endometriosis, PCOD tubal and peritoneal factors, uterine anomalies, tuberculosis etc. by using diagnostic laparoscopy. Although India's population growth is a serious issue, infertility seems to affect 5- 15% of Indians. Each of these patients has to be assessed. Infertility can be diagnosed with the use of laparoscopy. Following a complete clinical examination and targeted investigations, a diagnostic laparoscopy is carried out to look for morphological anomalies in the uterus, ovaries, and tuboperitoneum as well as tube patency. The study involved 60 infertile patients who visited the outpatient departments of the Tumkur hospitals affiliated with Sri Siddhartha Medical College. Patients with infertility, both primary and secondary, who underwent diagnostic laparoscopy and were eager to conceive were assessed. The surgery was not performed on those who were unwilling or ineligible. 72% of patients with basic infertility and 28% of individuals with secondary infertility had diagnostic laparoscopy. The majority of patients with initial infertility were between the ages of 21 and 25; those with secondary infertility were between 26 and 30. The majority of patients in both groups had been infertile for 1 to 5 years. In our investigation, the majority of the reasons of infertility were due to tubal factors (50%) in some way. The rate of complications was low and comparable to previous mainstream research. The gold standard for identifying endometriosis, tubal and peritoneal illness, and other pelvic pathologies is laparoscopic since no other imaging approach has the same level of sensitivity or specificity. Laparoscopy for diagnostic purposes is therefore a crucial technique in the assessment of infertility.